Avaliação do potencial antimicrobiano de extratos de folhas e sementes de Moringa oleifera LAM. frente à microrganismos patogênicos - Nascimento, Maria Helena do (2022)
Given the current scenario of antimicrobial resistance, the search for new drugs from natural products derived from plants has great biotechnological potential. Used in traditional medicine and popularly known as the “miracle tree”, Moringa oleifera has several biological properties, including antimicrobial and antioxidant activity. Thus, this research aimed to evaluate the antimicrobial and antioxidant activity of extracts from fresh and dried leaves, and seeds of M. oleifera, as well as to determine their phytochemical composition. Aqueous, methanolic and ethanolic extracts of leaves and seeds of M. oleifera were made, which were analyzed for antimicrobial activity through the agar diffusion test against strains of Staphylococcus aureus (ATCC 25923), methicillin-resistant S. aureus (MRSA 712, 984, R2 and S1), Enterococcus feacalis, Bacillus cereus, Pseudomonas aeruginosa, Escherichia coli and the yeast Candida albicans. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined by the dilution test in 96-well microplate. The antioxidant activity of the extracts was evaluated by the 2,2 diphenyl-1- picrylhydrazyl (DPPH) radical scavenging capacity test. The phytochemical composition of the extracts was analyzed by determining the content of total phenolic compounds in all tested extracts, and by mass spectrometry-coupled liquid chromatography (HPLC-MS) for ethanolic and methanolic extracts of dried leaves. It was found that the ethanolic extracts of dried leaves and moringa seeds had the highest yields. The aqueous extracts of fresh leaves and seeds showed the highest antimicrobial activity against strains B. cereus, E. faecalis, S. aureus and MRSA S1, R2, 712 and 984, while strains E. coli, P. aeruginosa and C. albicans showed resistance to all extracts. The lowest MICs were verified for the fresh leaf extract for E. faecalis (3.12 mg/mL), B. cereus (3.12 mg/mL) and S. aureus (0.78 mg/mL) and for the aqueous seed extract for MRSA S1 and R2 (0.78 mg/mL). In turn, the lowest CBM was observed for the aqueous extract of fresh leaves for B. cereus (6.25 mg/mL) and aqueous extract of seeds for MRSA R2 (0.78 mg/mL). All leaf extracts showed antioxidant activity, with the aqueous extract of dry leaves showing the highest activity (223.82 μg/mL), while the seed extracts had no antioxidant activity. The methanolic extract of dry leaves had the highest content of phenolic compounds (67.6525 mg EAG/g) and for seeds the aqueous extract (19.4279 mg EAG/g). The phytochemical profile of the ethanolic and methanolic extracts of dried leaves showed similarity and was represented by 18 compounds classified mostly as flavonoids and phenolic acids. The M. oleifera proved to be a promissory species for phytotherapeutic purposes, as it was confirmed as an antimicrobial agent against several bacteria, including methicillin-resistant S. aureus.